Effect of the laser intensity profile on the shock non-uniformity in a directly driven spherical target. (29th July 2015) - Temporal, Mauro; Canaud, Benoit; Garbett, Warren J.; Ramis, Rafael
Abstract : An axially symmetric laser beam configuration irradiating a spherical capsule has been considered in the context of inertial confinement fusion (ICF). The laser beams are located at co-latitudes 49° and 131° and mimic the quad positions in the second cone of the Laser Mégajoule Facility. The capsule is directly irradiated by the laser beams whose energy deposition generates a nearly spherical shock wave. Two-dimensional hydrodynamic numerical simulations have been performed to analyse the non-uniformity of the shock wavefront launched inward throughout the target. Different laser intensity profiles, calculated by the illumination model, have been tested. The performance, in terms of shock non-uniformity, has been compared, and it is found that with an appropriate choice of the laser intensity profile it is possible to control the shock non-uniformity at early times.